Love potion - Launer, Dale (Beverly Hills, California Twentieth Century Fox Home Entertainment, 1992)
In this charming romantic comedy, a brilliant but lonely biochemist gets a nysterious potion from a gypsy who guarantees it will turn his life around. After showing it to his co-worker, a shy animal psychobiologist, they achieve amazing amorous results in a chimpanzee experiment. Now the only way to see if it works on humans is to test it on themselves.
Executive producer, Thomas M. Hammel ; Film director, Suzanne Pettit.
Tate Donovan, Sandra Bullock, Mary Mara, Dale Midkiff, Hillary Bailey Smith, Dylan Baker.
Dolby digital.
In English with Spanish and English subtitles.
Keywords: Aphrodosiacs -- Drama; Love -- Drama